2021
DOI: 10.20892/j.issn.2095-3941.2020.0501
|View full text |Cite
|
Sign up to set email alerts
|

SHP-1 acts as a tumor suppressor by interacting with EGFR and predicts the prognosis of human breast cancer

Abstract: Objective:The aims of this study were to examine the prognostic value of SHP-1 in breast cancer, its roles in the regulation of breast cancer cell growth and metastasis, and the underlying mechanisms. Methods: Tumor specimens from 160 patients with breast cancer and 160 noncancerous tissues were used to examine the expression of SHP-1 and to analyze its association with overall survival through Kaplan-Meier and multivariate Cox regression analyses. RNA sequencing data and the expression and clinical importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…This suggests that the role of SHP1 in non‐hematopoietic cells requires further validation. Exogenous expression of SHP1 in these cells shows anti‐proliferative, anti‐migratory, and anti‐invasive effects, implying that SHP1 also functions as a tumor suppressor in non‐hematopoietic cancers 49,50 . Recent studies have shown that SHP1 silencing is prevalent in gastric adenocarcinoma tissues 51 and that its full activation prevents H. pylori ‐infected cells from forming the “hummingbird” phenotype, indicating its negative roles in the development of H. pylori‐ associated gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the role of SHP1 in non‐hematopoietic cells requires further validation. Exogenous expression of SHP1 in these cells shows anti‐proliferative, anti‐migratory, and anti‐invasive effects, implying that SHP1 also functions as a tumor suppressor in non‐hematopoietic cancers 49,50 . Recent studies have shown that SHP1 silencing is prevalent in gastric adenocarcinoma tissues 51 and that its full activation prevents H. pylori ‐infected cells from forming the “hummingbird” phenotype, indicating its negative roles in the development of H. pylori‐ associated gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous expression of SHP1 in these cells shows anti-proliferative, anti-migratory, and anti-invasive effects, implying that SHP1 also functions as a tumor suppressor in non-hematopoietic cancers. 49,50 Recent studies have shown that SHP1 silencing is prevalent in gastric adenocarcinoma tissues 51 and that its full activation prevents H. pylori-infected cells from forming the "hummingbird" phenotype, indicating its negative roles in the development of H. pylori-associated gastric cancer. Although the cancer-promoting effect of SHP2, the homolog of SHP1, on H. pylori-associated carcinogenesis has been extensively studied, the specific roles of SHP1 in this process remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…The association between SHP-1 expression and patient survival differs based on tumor type ( Table 1 ). High levels of SHP-1 expression are related to high survival rates in patients with tumors, including breast cancer, esophageal squamous cell carcinoma, hepatocellular carcinoma, and prostate cancer [ 20 , 33 , 34 , 35 , 36 , 37 ]. Additionally, there is a report on the antitumor function of SHP-1 in gastric cancer, although it is not associated with SHP-1 expression [ 38 ].…”
Section: Shp-1 Expression In Tumorsmentioning
confidence: 99%
“…More importantly, loss of PTPN2 is coupled with activation of oncogenic signaling pathways, such as protein kinase B (AKT), Src family kinase (SFK) and STAT3 signaling pathways, and also with resistance to tamoxifen ( 29 , 30 ). PTPN6 dampens the oncogenic characteristics of breast cancer by dephosphorylating STAT3 and inactivating the Ras/extracellular signal-regulated kinase (Erk)/glycogen synthase kinase-3beta (GSK-3β) signaling pathway ( 31 , 32 ). PTPN9 suppresses the growth and invasion of breast cancer cells by negatively regulating HER2 and epidermal growth factor receptor (EGFR) and suppressing STAT3 activation ( 33 , 34 ).…”
Section: Role Of Ptpns In the Context Of Cancermentioning
confidence: 99%